Faith on the Waves: Empowering Pameungpeuk of Garut Fishermen Through Spiritual Guidance - Nurlinah, Nurlinah (FISIP UIN SGD Bandung, 2025)
This study examines the role of religious motivators in enhancing the spiritual life of coastal communities at Pameungpeuk Beach. It focuses on three key aspects: the state of religious life prior to intervention, the identification of relevant religious materials, and the strategies employed by motivators to guide the community toward spiritual and social transformation. The study employs a qualitative descriptive method, gathering data through observations, interviews, and document analysis, with participants including fishermen, mosque administrators, and local leaders. The findings reveal that religious mentorship addressing the principles of faith, sharia, and morality significantly improved the community's spiritual engagement and understanding of Islamic practices. Faith-building initiatives tailored to the community's daily experiences strengthened their connection to religious teachings, while practical workshops on worship practices addressed prior knowledge gaps. Moral teachings fostered values such as honesty and cooperation, leading to broader social and economic improvements. This research highlights the transformative potential of a mosque-centered, contextual approach in addressing the unique challenges of coastal communities. It demonstrates the vital role of mosques as spiritual, educational, and social hubs, underscoring the importance of transparency and inclusivity in mosque management. The findings contribute to global discussions on community-based spiritual formation and offer a replicable model for similar contexts worldwide. By revitalizing the function of mosques and integrating religious teachings with everyday life, this study presents a sustainable pathway for fostering optimism, resilience, and social cohesion in underserved communities.